Book reviews: Thomas L. Friedman – Hot, flat and crowded. Why the world needs a green revolution – and how we can renew our global future - Uţă, Cristian (Annals of Spiru Haret University. Economic Series, 2011)
In his latest book, Hot, Flat and Crowded, the triple Pulitzer award laureate, Thomas Friedman, foreign affairs analyst and columnist at ”The New York Times”, succeeds a thorough and well-grounded analysis of the weather changes in the present and of the measures to be taken in the near future.